Ekuitas Pemanfaatan Jaminan Kesehatan Nasional (JKN) dalam Mewujudkan Universal Health Coverage (UHC) di Kecamatan Medan Baru - Fenny Dwi Arini; Fitriani Pramita Gurning (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
Indonesia's health system is transitioning to UHC, to achieve UHC the government established the JKN program with an agreement to improve UHC achievements in the degree of public health in Indonesia. In 2019 the low number of JKN participation in Medan Baru District was 31,758 participants from 41,149 people (77%) The data showed the low utilization of JKN in Medan Baru District. Therefore , researchers want to know what factors affect the utilization of JKN in Medan Baru District. The method in this study is quantitative with a cross sectional design. The sample of this study was 100 respondents with a random sampling cluster sampling technique. In the Chi Square Test Results there was no relationship between age (0.599>0.05), gender (0.337>0.05), employment (0.062>0.05), income (0.586>0.05) with the utilization of JKN, because there was a relationship between participation (0,000<0.05), knowledge (0.030<0.05), attitude (0.000<0.05), and family support (0.000<0.05) with the utilization of JKN. And in the Results of The Logistic Regression Test the variables that affect are on the variables of knowledge (p>0.027) and Exp (B) 5,760 dan variabel Family Support (p>0.031) and Exp (B) 4,416. The conclusion is that there is no influence between age, gender, occupation, income, participation and attitude with the utilization of JKN in Medan Baru District. And the influence between knowledge and family support with the utilization of JKN in Medan Baru Subdistrict.